Leonotis nepetaefolia R. Br. - a Less Known Medicinal Plant - Verma, N. K.; Singh, P. K.; Kumar, P.; Sharma, A.; Hore, D. K. (Indian Forester, 2003)
Leonotis nepetaefolia R. Br. (Laminaceae) is an attractive, symmetrical, annual medicinal plant. A brief description of the plant is described in the present article. The plant is believed to be a native of Africa and the distribution extends to tropical Asia and America. It has been cultivated in Brazil since long. The plant seems to have naturalized in India. Traditionally, the leaf is used in rheumatic affections and also serves as a tonic. Flower heads are used against scalds, burns, ringworm, and some skin diseases. Crushed root is applied locally for facilitating breast milk to a mother after childbirth. Seeds are used in fever. It has also got the anticancer, antioxidant and antibacterial properties. In India, it grows wild but not common. In recent years, India has given due attention on this plant to develop it’s agrotechniques for commercial cultivation. Accordingly, responsibilities were entrusted with the NBPGR Regional Station, Shillong since 1999.